Computational Contact Mechanics - Wriggers, Peter.; Wriggers, Peter.; Laursen, Tod A.; Laursen, Tod A. (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2007)
Topics of this book span the range from spatial and temporal discretization techniques for contact and impact problems with small and finite deformations over investigations on the reliability of micromechanical contact models over emerging techniques for rolling contact mechanics to homogenization methods and multi-scale approaches in contact problems. Furthermore, solution algorithms for single- and multi-processor computing environments, enabling methods that span from multi-contact to multi-scale approaches are discussed together with numerical experiments related to soil mechanics using discontinuous deformation analysis.